Estimates and demographic correlates of hoarding disorder in non-clinical sample in Pakistan - Ayesha Inam; Zubaa Akhtar; Aisha Kashif; Hamna Nadeem (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To establish sample estimates of hoarding behaviour with demographic correlates in a non-clinical sample. Method: The cross-sectional study was conducted in Islamabad, Pakistan, from February to April, 2018, and comprised data collected from Karachi, Lahore, Islamabad and Rawalpindi after approval from the COMSATS University, Islamabad. Data was collected using a self-developed demographic sheet, along with the hoarding rating scale. Data was analysed using SPSS, Version 20. Results: Of the 375 subjects, 118(31.5%) were males and 257(68.5%) were females. The overall mean age was 42.25+/-13.007 years. Mean hoarding rating scale score was 8.34+/-6.69, with 76(20.3%) subjects falling in the clinical range of hoarding tendencies. There was a significant difference in the scores for Early Adulthood, Middle Adulthood and Late Adulthood (p<0.001). Gender comparison revealed significant difference (p<0.001). A significant positive correlation between hoarding and age was found (p<0.01) whereas a negative correlation was found between hoarding and monthly household income (p<0.01). Conclusion: Hoarding tendencies were found to be in the clinical range for one-fifth of the sample. Key Words: Hoarding disorder, Estimates, Demographics, Continuou...